Evaluation of nitrogen sources for growth and production of medium-chain-length poly-(3-Hydroxyalkanoates) from palm kernel oil by pseudomonas putida PGA1 - Annuar, M.S.M.; Tan, I.K.P.; Ramachandran, K.B. (2008)
Selected organic and inorganic nitrogen sources were evaluated for growth of Pseudomonas putida PGA1 and its production of medium-chain-length poly-(3-hydroxyalkanoates) (PHAMCL). The effect of these nitrogen sources on the cells growth, PHAMCL yield, monomer composition and molecular weight when this bacterium was cultivated on saponified palm kernel oil (SPKO) as the major carbon source was investigated. It was found that bacto-peptone gave significantly higher yield of residual biomass (PHA-free biomass) and PHAMCL as compared to ammonium salt, urea, yeast extract and beef extract. No significant difference in the monomer composition of the PHAMCL produced was observed with the different nitrogen sources. All the PHAMCL produced had high molecular weight, with the weight average (Mw) ranging from 90,000 to 127,000 and polydispersities (Mw/Mn) ranging from 1.7 to 1.9.